Measuring the Level of Community Satisfaction with Government Services in Pino Raya District, South Bengkulu Regency - Nela Puspita Sari; Karona Cahya Susena; Nia Indriasari (Penerbit Jurnal Indonesia, 2020)
This study aims to determine the level of community satisfaction index with government services in Pino Raya Sub-District, South Bengkulu Regency. The research method used is descriptive quantitative approach in which the sample was 100 respondents with the data collection technique using a questionnaire. This research instrument as stated in the Regualation of the Minister of Administrative Reform and Bureaucratic Reform Number 14 of 2017 concerning Guidelines for Preparing a Community Statisfaction Survey in Pino Raya SubDistrict, South Bengkulu Regency has been running well. This can be seen from the 9 appropriate indicator (Permenpan-RB) Number 14 of 2017 it can be concluded that the Very Good indicator is in Costs/Rates, Good Indicators are in Implementing Behavior, Facilities and Infrastructure , while Poor Indicators are in Requirements Indicators, Mechanisme Systems and Procedures, Time of Completion, Product Specifications, Competence of Implementers and Complaint Handling for suggestions and input. The conclusion is that the average value of the Pino Raya Sub-District Government of South Bengkulu Regency is Good.